Coupled Modes of North Atlantic Ocean‐Atmosphere Variability and the Onset of the Little Ice Age. Issue 21 (7th November 2019) - Anchukaitis, Kevin J.; Cook, Edward R.; Cook, Benjamin I.; Pearl, Jessie; D'Arrigo, Rosanne; Wilson, Rob
Abstract: Hydroclimate extremes in North America, Europe, and the Mediterranean are linked to ocean and atmospheric circulation anomalies in the Atlantic, but the limited length of the instrumental record prevents complete identification and characterization of these patterns of covariability especially at decadal to centennial time scales. Here we analyze the coupled patterns of drought variability on either sides of the North Atlantic Ocean basin using independent climate field reconstructions spanning the last millennium in order to detect and attribute epochs of coherent basin‐wide moisture anomalies to ocean and atmosphere processes. A leading mode of broad‐scale moisture variability is characterized by distinct patterns of North Atlantic atmosphere circulation and sea surface temperatures. We infer a negative phase of the North Atlantic Oscillation and colder Atlantic sea surface temperatures in the middle of the fifteenth century, coincident with weaker solar irradiance and prior to strong volcanic forcing associated with the early Little Ice Age. Key Points: Atlantic ocean‐atmosphere circulation links drought in North America, Europe, and the Mediterranean Coupled modes of drought variability can be used to infer atmospheric circulation and ocean temperature anomalies Coupled terrestrial drought patterns reveal the start of the Little Ice Age to be characterized by a negative NAO and cold Atlantic SSTs